Action of plant proteinase inhibitors on enzymes of physiopathological importance - Oliva,Maria Luiza V. (2009)
Obtained from leguminous seeds, various plant proteins inhibit animal proteinases, including human, and can be considered for the development of compounds with biological activity. Inhibitors from the Bowman-Birk and plant Kunitz-type family have been characterized by proteinase specificity, primary structure and reactive site. Our group mostly studies the genus Bauhinia, mainly the species bauhinioides, rufa, ungulata and variegata. In some species, more than one inhibitor was characterized, exhibiting different properties. Although proteins from this group share high structural similarity, they present differences in proteinase inhibition, explored in studies using diverse biological models.